Memanfaatkan Media Sosial untuk Meningkatkan Partisipasi Generasi Muda Menjaga Lingkungan - Safira, Mirza Elmy; Apsari, Angelina Cahya Dwi; Mardikaningsih, Rahayu; Vitrianingsih, Yeni; Masfufah, Masfufah (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Service (PkM) activity aims to optimize the use of social media as a means of empowering the younger generation in environmental protection. The method used is Participatory Action Research (PAR) through analysis of social media content, location-based environmental issues, and direct involvement of youth in conservation campaigns and activities. The results of the activity show that social media is effective as a medium for education, mobilizing action, and forming environmental care communities that have an impact on increasing awareness, participation, solidarity, and collaboration among youth. Digital platforms have also proven to be able to promote environmental activities widely and quickly. However, the consistency of involvement in real actions and sustainable education programs still needs to be strengthened through mentoring and more systematic communication strategies. Thus, the integration of relevant, authentic, and easy-to-understand environmental narratives in social media is a key strategy to increase the practical participation of the younger generation while strengthening community-based conservation movements.